THE TEACHERS’ STRATEGIES ON TEACHING READING COMPREHENSION OF RECOUNT TEXT AT GRADE X OF SMA NEGERI 1 SIMPANG EMPAT - Dessyana Nasution; Masitowarni Siregar (Universitas Negeri Medan, 2017)
The aims of this study are to know the Teachers’ Strategies on Teaching Reading Comprehension of Recount Text at Grade X of SMA Negeri 1 Simpang Empat. It was conducted by using qualitative research method. The subjects of this study are two English teachers at SMA Negeri 1 Simpang Empat. The two teachers taught at Grade X. They chosen as the subject which were observed and interviewed. The writer used two instruments, they were observation and interview. This study found that the teachers at SMA Negeri 1 Simpang Empat used appropriate strategy in teaching reading comprehension of recount text and using the media to make the students be motivated and interested in learning. The teachers guided and managed the students in comprehending the material. The teachers' reason in using strategies is because the students get difficulties in comprehending the material if the teachers were used the traditional teaching strategies. The implementation of the strategy adapted by the teachers with the material, the indicator, the purpose of learning on the syllabus and curriculumn. All of the students were active and motivated in teaching and learning process. They were also brave to share the idea, asked the teacher when they found the problem on learning the material and answer the question that given by the teacher.